333 Impact of extent of cytoreductive surgery (CRS) on survival in epithelial ovarian cancer (EOC), primary peritoneal carcinomatosis (PPC), and fallopian tube cancer (FTC) at the american university of beirut (AUBMC). (18th September 2019) - Seoud, M; El Housheimi, A; Jaafar, I; Hamed, K; Jamali, F; Abdallah, R; Khalil, A
Abstract : Objectives: To study the impact of the extent of CRS [complete Debulking (CD), optimal Debulking (OD)<1cm, or suboptimal Debulking (SOD) >1cm residual disease] on progression free (PFS) and overall survival (OS) in advanced EOC, PPC and FTC treated at AUBMC 1998–2018. Methods: We retrospectively reviewed all patients with advanced disease who underwent either Primary debulking surgery (PDS) or if they had large tumor burden/multiple co-morbidities/poor performance status, they received neoadjuvant chemotherapy and interval debulking surgery (NACT+IDS). Results: Of 300 patients with EOC/PPC/FTC, 220 had advanced stages (IIIB-IV). 66.4% had CD, 29.7% OD and 2.6% SOD. Results are shown in image 1 and tables 2 and 3. Median survival is expressed in months. In stage IIIC, CD led to a significantly higher PFS compared to OD (image 1 ) (P-value=0.015). However, this increase in PFS was only seen after IDS (table 2 ) (P-value in IDS=0.009). Once a CD was reached, There was no statistically significant increase in PFS regardless of timing of CRS (Image 3) (Pvalue=0.775). OS was not affected by extent of CRS (Image 1 ). Conclusions: The extent of CRS significantly prolonged PFS but not OS in stage IIIC but not IV. This increase in PFS is only seen after IDS. Patients having CD have similar PFS and OS regardless of the timing of CRS.